2009
DOI: 10.1074/jbc.m807747200
|View full text |Cite
|
Sign up to set email alerts
|

Solution NMR Structure of the C-terminal EF-hand Domain of Human Cardiac Sodium Channel NaV1.5

Abstract: The voltage-gated sodium channel Na V 1.5 is responsible for the initial upstroke of the action potential in cardiac tissue. Levels of intracellular calcium modulate inactivation gating of Na V 1.5, in part through a C-terminal EF-hand calcium binding domain. The significance of this structure is underscored by the fact that mutations within this domain are associated with specific cardiac arrhythmia syndromes. In an effort to elucidate the molecular basis for calcium regulation of channel function, we have de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
93
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 43 publications
1
93
0
Order By: Relevance
“…Thus, endogenous CaMKII may be activated by 1 M pipette Ca 2ϩ (32), but higher levels of CaMKII were necessary for maximal functional effects. The potent peptide CaMKII inhibitor AIP was included to verify that changes in I Na were due to CaMKII and not direct effects of Ca 2ϩ (33)(34)(35)(36) and/or Ca 2ϩ / CaM (34,35,(37)(38)(39)(40)(41). We found that Ala point mutations at Ser-516 and Thr-594 identified in our biochemical phosphorylation assays disrupted CaMKII-induced alterations in I Na gating.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, endogenous CaMKII may be activated by 1 M pipette Ca 2ϩ (32), but higher levels of CaMKII were necessary for maximal functional effects. The potent peptide CaMKII inhibitor AIP was included to verify that changes in I Na were due to CaMKII and not direct effects of Ca 2ϩ (33)(34)(35)(36) and/or Ca 2ϩ / CaM (34,35,(37)(38)(39)(40)(41). We found that Ala point mutations at Ser-516 and Thr-594 identified in our biochemical phosphorylation assays disrupted CaMKII-induced alterations in I Na gating.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of Ca 2+ , the apo-CaM C lobe binds to the IQ motif of neuronal (30,32,33) and cardiac isoforms (5,6,8,29,30,34). Introduced or inherited mutations to either EF hands or IQ motifs can abolish Ca 2+ -dependent effects on inactivation (6,7,11,28); however, the ability of the EF-hand region to bind Ca 2+ ions directly remains contentious (7,8,11,28,35). Importantly, it is not known how Ca 2+ or Ca 2+ /CaM interactions with the C-terminal EF-hand and IQ motifs are relayed to channel inactivation, but we (9) and others (10) Table S4. in Ca 2+ regulation, a possibility suggested previously (28).…”
Section: Discussionmentioning
confidence: 99%
“…Together, these experiments demonstrate that the observed Ca 2+ /CaM interaction in the crystal structure and the ITC characterizations are physiologically relevant, and that the DIII-IV linker is the final site of action for Ca 2+ /CaM regulation of channel inactivation. The exact mechanism by which CaM might interact with the fulllength C terminus has not been elucidated, but it is known that the IQ and EF-hand motifs undergo Ca 2+ -dependent conformational changes and can bind CaM in the presence and absence of Ca 2+ (11,29,30). Data in Fig.…”
Section: Diii-iv Linker Is the Physiological Endpoint For Camentioning
confidence: 99%
See 1 more Smart Citation
“…Structure of the C-terminal Ef-hand domain of human cardiac sodium channel. Available from http://www.ncbi.nlm.nih.gov/Structure/mmdb/mmdbsrv.cgi?uid=68594 (Chagot et al, 2009). …”
Section: Other Genes Involved In Development Of Dcmmentioning
confidence: 99%